PENDIDIKAN TOLERANSI DALAM HADITS NABI SAW - Agung Setiyawan (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2015)
Religious harmony should be realized by mutual respect among fellow adherents. The fact that happened in the life of society still found various cases of intolerance. This is a problem that needs to find a solution. Understanding of the teachings and religious education is indispensable for fostering harmony. Therefore, this paper discusses the hadith of the Prophet on the teachings of tolerance by analyzing hadiths. Conclusions of this study found that the Tolerance in Islam does not mean being syncretic which can lead to mixing between the right and wrong (al-haq talbisu bi al-bathil), as syncretic attitude is an attitude that considers all religions equally. While tolerance in Islam is respect and honor the faith and other religions outside of Islam, not equate or mensederajatkannya the Islamic faith itself and Islam tolerates long as it is not related to the Aqeedah (belief).